Expanding Holocaust Cartography: Memory Maps as Testimonies - Szczepan, Aleksandra (Holocaust and genocide studies, 2025)
This article posits that maps are awkward and underutilized documents in Holocaust studies. Although maps serve many testimonial purposes, researchers have often viewed them as peripheral documents, especially when compared to written and spoken testimonies. By centering the maps of victims of the Treblinka death camp and the hand-drawn maps appearing in postwar memorial books, the authors draw attention to maps' ambiguous standing as archival sources, as well as the unique histories they communicate. This article critically analyzes maps to show how they reveal the geography of the genocide, as well as the integration of Jewish communities in Eastern Europe.